Methodist Spiritual Condition in Georgian Northern England - Schofield, Robert A. (The journal of ecclesiastical history, 2014)
John Wesley required detailed records to be compiled of Methodist society members. One extant list is that of the Keighley circuit for 1763–5. This article, breaking new ground in Wesley studies, argues that symbols in this and other catalogues recorded members’ spiritual condition. These symbols are used to analyse recruitment, losses and spiritual change on a quarterly basis. They reveal that although recruitment in the circuit was high during a revival at the start of a new preaching regime, it fell quickly, many members departed and there was little overall improvement in spiritual condition. Recruitment and changes were not uniform across the circuit, pointing to local rather than regional or national influences.